Study protocol for Women of Color and Asthma Control: A randomized controlled trial of an asthma-management intervention for African American women - Janevic, Mary R (BioMed Central, 2012)
BACKGROUND: Among adults in the United States, asthma prevalence is disproportionately high among African American women; this group also experiences the highest levels of asthma-linked mortality and asthma-related health care utilization. Factors linked to biological sex (e.g., hormonal fluctuations), gender roles (e.g., exposure to certain triggers) and race (e.g., inadequate access to care) all contribute to the excess asthma burden in this group, and also shape the context within which African American women manage their condition. No prior interventions for improving asthma self-management have specifically targeted this vulnerable group of asthma patients. The current study aims to evaluate the efficacy of a culturally- and gender-relevant asthma-management intervention among African American women. METHODS/DESIGN: A randomized controlled trial will be used to compare a five-session asthma-management intervention with usual care. This intervention is delivered over the telephone by a trained health educator. Intervention content is informed by the principles of self-regulation for disease management, and all program activities and materials are designed to be responsive to the specific needs of African American women. We will recruit 420 female participants who self-identify as African American, and who have seen a clinician for persistent asthma in the last year. Half of these will receive the intervention. The primary outcomes, upon which the target sample size is based, are number of asthma-related emergency department visits and overnight hospitalizations in the last 12 months. We will also assess the effect of the intervention on asthma symptoms and asthma-related quality of life. Data will be collected via telephone survey and medical record review at baseline, and 12 and 24 months from baseline. DISCUSSION: We seek to decrease asthma-related health care utilization and improve asthma-related quality of life in African American women with asthma, by offering them a culturally- and gender-relevant program to enhance asthma management. The results of this study will provide important information about the feasibility and value of this program in helping to address persistent racial and gender disparities in asthma outcomes. TRIAL REGISTRATION: ClinicalTrials.gov: NCT01117805